2007
DOI: 10.2307/25549731
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Meanings of Exchange of Money or Gifts for Sex in Unmarried Adolescent Sexual Relationships in Sub-Saharan Africa

Abstract: Using national survey data collected in 2004 in Burkina Faso, Ghana, Malawi, and Uganda with 12-19 year olds, we examine the prevalence of sex in exchange for money or gifts in the 12 months prior to the survey and its association with adolescents' social and economic vulnerability and condom use. Receiving something in exchange for sex is very common among sexually active, unmarried female adolescents and there are no significant differences by household economic status, orphan status, level of schooling comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
99
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 25 publications
10
99
3
Order By: Relevance
“…This study has revealed lower condom use compared to a study conducted in northeast Ethiopia [21]. This may be due to a difference in the socioeconomic characteristics of the respondent and differentiate in infrastructures.…”
Section: Discussioncontrasting
confidence: 67%
“…This study has revealed lower condom use compared to a study conducted in northeast Ethiopia [21]. This may be due to a difference in the socioeconomic characteristics of the respondent and differentiate in infrastructures.…”
Section: Discussioncontrasting
confidence: 67%
“…54 As was demonstrated in that analysis, in the majority of the narrations of sex involving money or gifts, the respondent did not make clear the role that money played in bringing about sexual intercourse. In Malawi, gifts were generally not described as having a coercive influence.…”
Section: Pressure From Gifts or Moneymentioning
confidence: 92%
“…This definition differentiates neither between cash versus material forms of exchange, nor between the payment and the gift form; it conflates these two dimensions. Even where surveys may ask what is precisely transferred, for instance, money, food, or clothing for sex, the analysis conflates these as ''money or gift'' transfers (Luke 2003(Luke , 2006Moore et al 2007). In other words, research rarely inquires into the symbolic meanings assigned by participants to the exchanged goods and to the transaction.…”
Section: Commercial Sex and Transactional Sexmentioning
confidence: 99%